Nurse participation in patient care after kidney transplant - Pluta, Agnieszka; Sulikowska, Beata; Budnik-Szymoniuk, Maria; Basińska-Drozd, Halina (Journal of Education, Health and Sport, 2017)
Kidney transplantation is considered to be the optimal treatment for end-stage renal disease. The main goal of renal replacement therapy is to prolong life as well as improve its quality. The key here is the education of the patient, which is conducted by a transplant physician, a transplant nurse and a nutritionist. Nursing staff taking care of a patient after a kidney transplant should have the ability to correctly diagnose and resolve nursing problems. The aim of the work is to present the role of a nurse in patient care after kidney transplant. Nurses pursuing health education focus primarily on shaping individual patient health behaviors.